Approaches to teaching Poe's prose and poetry - Weinstock, Jeffrey Andrew; Magistrale, Tony. (New York : Modern Language Association of America, 2008)
Contains essays that discuss different techniques that teachers can use to aid students to better understand the work of Edgar Allan Poe.
Preface to the series -- Preface to the volume -- Part One: Materials / Jeffrey Andrew Weinstock and Tony Magistrale -- Courses and texts -- Readings for students -- Readings for teachers -- Aids to teaching -- Part Two: Approaches -- Introduction / Jeffrey Andrew Weinstock and Tony Magistrale -- Literary, cultural and historical contexts -- Teaching Poe the magazinist / Scott Peeples -- Poe the crime writer: historicizing "The murders in the Rue Morgue" / Leonard Cassuto -- "Legitimate sources" and "legitimate results": surveying the social terror of "Usher" and "Ligeia" / Duncan Faherty -- "Some words with a mummy": teaching satire and the democratic threat in Poe's fiction / Edward Wesp -- Teaching the mechanics of deception: "Hans Pfall", science fiction, and hoaxing in antebellum print culture / Marcy J. Dinius -- What difference does it make? Pym, plagiarism, and pop culture / Jeffrey Andrew Weinstock -- Understanding the fear and love of death in three premature-burial stories: "The Premature Burial," "Morella," and "The fall of the House of Usher" / t
Includes bibliographical references (p. [217]-234) and indexes.
Keywords: Poe, Edgar Allan, -- 1809-1849 -- Study and teaching; Poe, Edgar Allan, -- 1809-1849 -- Criticism and interpretation; American literature -- Study and teaching (Higher); Poe, Edgar Allan; Englischunterricht; Hochschuldidaktik; Poe, Edgar Allan, -- 1809-1849.; Englischunterricht; Hochschuldidaktik; Poe, Edgar Allan, -- 1809-1849.; American literature -- Study and teaching (Higher); Study skills; Aufsatzsammlung; Aufsatzsammlung; Criticism, interpretation, etc